Pemberdayaan Masyarakat Kampung Benayah tentang Pengaruh Modal Politik terhadap Praktik Money Politic Studi Kasus: Pilwako Pekanbaru Tahun 2017 - Marta, Auradian; Indah, Dini Permata; Hsb, Aminah Rahmah; J, Gilang Ramadhani; Akmal, Sirajuddin; Sari , Elvina Mutia; Hsb, Siti Agustina; Saputra, Alziad; Sari , Sintia Eka Puspita; Afrizal, Afrizal; Irawan, M. Alfa Rizi; Balqis, Natasya Sabilla (Civiliza Publishing, 2024)
According to Birner Whitmer, 2007, the concept of political capital is an effort to support the achievement of political goals through an assessment of local social capital such as the use of campaign funds, active participation in elections, political negotiations and communication, mobilization of voter support, economic freedom, protest democracy, and efforts to advance democracy through the construction and negotiation of political models (Zerri et al., 2024). This study aims to determine the effect of political capital (campaign funds) on the practice of money politics and vote acquisition in the Pilkada contestation. The method used in this research is a literature study, where the data and information needed are obtained from textbooks, observation reports, scientific journals and from the internet. The results obtained are that political capital (campaign funds) has a significant influence on the practice of money politics that supports the vote acquisition of candidates in the Pilkada contestation. So, political capital in the form of large campaign funds has a significant influence and correlation on the practice of money politics and vote acquisition in the Pilkada contestation. Because candidates with large and strong political capital have political support from political coalitions or networks, so they will also have a wider position and power because they succeeded in winning the Pilkada.